Answer:
![\displaystyle f(x)=4\cdot\left((1)/(2)\right)^x](https://img.qammunity.org/2022/formulas/mathematics/high-school/2ws6cnv5am2zsjttdfx0tdiowd7o4svbiq.png)
Explanation:
Exponential Function
The exponential function can be written with the general equation:
![f(x)=A\cdot r^x](https://img.qammunity.org/2022/formulas/mathematics/high-school/tf4iue7ow4ol3ondj3xq1j18h1q6pizjkx.png)
Where A is the value when x=0 and r>0 is the ratio. If r is greater than 1, the function is increasing, if r is less than 1, the function is decreasing.
The table shows the relation between values of x and values of the function y. Note that as x increases (one by one), y decreases with a ratio of 1/2. Only the last two choices have ratios of r=1/2. We only have to test which one of them has the correct value of y=4 when x=0.
Substituting in the third function:
![\displaystyle f(x)=4\cdot\left((1)/(2)\right)^x](https://img.qammunity.org/2022/formulas/mathematics/high-school/2ws6cnv5am2zsjttdfx0tdiowd7o4svbiq.png)
![\displaystyle f(0)=4\cdot\left((1)/(2)\right)^0](https://img.qammunity.org/2022/formulas/mathematics/high-school/jv303xzr989b95rze0sam5ar2warjac687.png)
![f(0) = 4](https://img.qammunity.org/2022/formulas/mathematics/high-school/m5pbj8h06a3ol8uj1y8j46z5arbuthjug7.png)
This gives the correct value of f(0)=4.
Substituting in the fourth function:
![\displaystyle f(x)=(1)/(2)\cdot\left((1)/(2)\right)^x](https://img.qammunity.org/2022/formulas/mathematics/high-school/swhbh3nfbzftbgcyhpavuhnv24waco32sn.png)
![\displaystyle f(0)=(1)/(2)\cdot\left((1)/(2)\right)^0](https://img.qammunity.org/2022/formulas/mathematics/high-school/43gv3eu5q1hzufj2hvgz12y99jl9lyyyvq.png)
![f(0) = (1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/b2szu1pv3r24egjb0vzdpi6xaqjmiqj1n7.png)
This choice is wrong
Correct choice:
![\boxed{\displaystyle f(x)=4\cdot\left((1)/(2)\right)^x}](https://img.qammunity.org/2022/formulas/mathematics/high-school/71xldcz530yblsfn8ze2t3p53eja4tl5qe.png)